THE EFFECT OF GIVING GARLIC PEEL EXTRACT (Allium sativum) IN DRINKING WATER ON THE PERCENTAGE OF EXTERNAL OFFAL BROILER AGE 4 WEEKS ABSTRACT - I.A.S.T., Prabayanti; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2023)
This study aims to determine the effect of giving garlic peel extract in drinking water on the external offal percentage of broiler chickens age 4 weeks. This research was conducted in Banjar Selanbawak Kelod, Selanbawak Village, Marga District, Tabanan Regency, Bali which was carried out for 4 weeks. The design used was a completely randomized design with 4 treatments and 4 replications each containing 5 broilers, so that 80 bird total number of broilers was used . The treatments were :broiler chickens that were given drinking water without garlic peel extract (P 0 /Control), drinking water with 1% garlic peel extract (P 1 ), drinking water with 2% garlic peel extract (P 2 ), drinking water with 3% garlic peel extract (P 3 ). The variables observed were percentage of the head, percentage of the neck, percentage of the legs, percentage of the blood, and percentage of the feather. The results showed that the treatment of giving 1%-3% garlic peel extract through drinking water had non significant effect (P<0.05) on the percentage of head, neck, legs, feathers and blood of 4 weeks old broilers. The addition of garlic peel extract in drinking water had a significant effect (P>0.05) on the percentage of broiler necks. From this study, it can be concluded that giving garlic peel extract as much as 1%, 2%, and 3% in drinking water has no effect on percentage of external offal (head, neck, legs, blood, and feathers) of broiler chickens aged 4 weeks.   Keywords : broiler chickens, external offal, garlic peel extract